Diverse paths in improving broadband availability: Deductive inference from the perspective of neo-institutional economics - Nahoko Mitsuyama; Hitoshi Mitomo (International Telecommunications Society (ITS), 2012)
This paper aims at deducing how different owner-management relations of operators lead them and a regulator to make different decisions with regard to broadband, by adopting an approach of neo-institutional economics and a model based on game theory. Out of five modes that Aoki (2010) proposes as types of corporate organization, H- and S-modes are studied in this research, which used to be typically observed in general in the United States and Japan respectively. First, it is deduced that operators in each mode makes different decisions on broadband businesses affected by the respective natures of owner-management relations. Then a model of unbundle regulation game is applied to both modes, and combinations of best strategies for each are found to be exactly the opposite: (no unbundle regulation, no additional broadband investments, no entrance) for the regulator, the incumbent and the competitor in H-mode case, while (unbundle regulations, additional investments, entrance) in S-mode. Short case studies of the United States and Japan support the model's validity temporarily, though closer investigations are required. This result indicates that the owner-management relations of operators can determine the effectiveness of unbundle regulation, and suggest that they should be taken into account when practitioners examine possible measures.
Keywords: 330